In situ longitudinal pre-stretch in the human femoropopliteal artery. (1st March 2016) - Kamenskiy, Alexey; Seas, Andreas; Bowen, Grant; Deegan, Paul; Desyatova, Anastasia; Bohlim, Nick; Poulson, William; MacTaggart, Jason
Graphical abstract: Abstract: In situ longitudinal (axial) pre-stretch (LPS) plays a fundamental role in the mechanics of the femoropopliteal artery (FPA). It conserves energy during pulsation and prevents buckling of the artery during limb movement. We investigated how LPS is affected by demographics and risk factors, and how these patient characteristics associate with the structural and physiologic features of the FPA. LPS was measured in n = 148 fresh human FPAs (14–80 years old). Mechanical properties were characterized with biaxial extension and histopathological characteristics were quantified with Verhoeff–Van Gieson Staining. Constitutive modeling was used to calculate physiological stresses and stretches which were then analyzed in the context of demographics, risk factors and structural characteristics. Age had the strongest negative effect ( r = −0.812, p < 0.01) on LPS and could alone explain 66% of LPS variability. Male gender, higher body mass index, hypertension, diabetes, coronary artery disease, dyslipidemia and tobacco use had negative effects on LPS, but only the effect of tobacco was not associated with aging. FPAs with less pre-stretch had thicker medial layers, but thinner intramural elastic fibers with less dense and more fragmented external elastic laminae. Elastin degradation was associated with decreased physiological tethering force and longitudinal stress, while circumferential stress remained constant. FPA wall pathology was negatively associated with LPS ( r = −0.553, p < 0.01), but the effect was due primarily to aging. LPS in the FPA may serve as an energy reserve for adaptive remodeling. Reduction of LPS due to degradation and fragmentation of intramural longitudinal elastin during aging can be accelerated in tobacco users. Statement of Significance: This work studies in situ longitudinal pre-stretch (LPS) in the human femoropopliteal artery. LPS has a fundamental role in arterial mechanics, but is rather poorly studied due to lack of direct in vivo measurement method. We have investigated LPS in the n = 148 human femoropopliteal arteries in the context of subject demographics and risk factors, and structural and physiologic characteristics of the artery. Our results demonstrate that LPS reduces with age due to degradation and fragmentation of intramural elastin. LPS may serve as an energy reserve for adaptive remodeling, and reduction of LPS can be accelerated in tobacco users.